2021
DOI: 10.12669/pjms.37.3.3469
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between monocyte to high-density lipoprotein ratio and major adverse cardiovascular events in patients with acute coronary syndrome after percutaneous coronary intervention

Abstract: Objective: To investigate the correlation between monocyte to high-density lipoprotein ratio (MHR) and major adverse cardiovascular events (MACE) in patients with acute coronary syndrome (ACS) after percutaneous coronary intervention (PCI). Methods: In this retrospective study, 120 ACS patients who received PCI in our hospital from September 2014 to August 2019 were selected and divided into MACE group and normal discharge (ND) group. Their clinical data were collected, and MHR values were compared. Logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…[ 18 , 20 ] Subgroup analysis according to sample size, and follow-up showed pooled HR estimates with similar results to that of the original analysis. Interestingly, STEMI patients (HR = 2.66, 95% CI 1.62–4.35, P < .001) [ 14 , 19 ] with high MHR tend to have a higher risk of developing long-term MACEs than ACS patients (HR = 1.41, 95% CI 1.15–1.73, P = .001). [ 13 , 17 , 18 , 20 ] The subgroup analysis results of HR values for long-term MACEs were shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 18 , 20 ] Subgroup analysis according to sample size, and follow-up showed pooled HR estimates with similar results to that of the original analysis. Interestingly, STEMI patients (HR = 2.66, 95% CI 1.62–4.35, P < .001) [ 14 , 19 ] with high MHR tend to have a higher risk of developing long-term MACEs than ACS patients (HR = 1.41, 95% CI 1.15–1.73, P = .001). [ 13 , 17 , 18 , 20 ] The subgroup analysis results of HR values for long-term MACEs were shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…These studies were all observation researches and were conducted in China, [15,[17][18][19][20] and Turkey. [13,14,16,21] One study included CAD patients, [15] 3 studies included ST-segment elevation myocardial infarction (STEMI) patients, [14,16,19] and 5 studies ACS patients. [13,17,18,20,21]…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…MHR has been shown to be associated with many diseases, including acute ischemic Stroke (AIS), primary nephrotic syndrome (NS) and Parkinson's disease (PD) [16][17][18]. Meanwhile, a recent cross-sectional study has found that MHR is associated with the incidence of NAFLD [19], and that MHR is associated with a variety of cardiovascular events and has been shown to be positively associated with adverse cardiovascular outcomes [20,21]. However, data on the relationship between MHR and CAD risk in NAFLD patients are not yet available.…”
Section: Introductionmentioning
confidence: 99%